2021
DOI: 10.3390/en14112977
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Small Hydropower Generation Potential: (1) Estimation of the Potential in Ungaged Basins

Abstract: Small hydropower (SHP) plants are advantageous as they have a short construction period and can be easily maintained. They also have a higher energy density than other alternative energy sources as environmentally-friendly energy sources. In general, hydropower potential is estimated based on the discharge in the river basin, and the discharge can be obtained from the stage station in the gaged basin. However, if there is no station (i.e., ungaged basin) or no sufficient discharge data, the discharge should be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The discharge was calculated using several runoff formulas and hydrologic models and blending techniques have been proposed to reduce the uncertainty of the results and to increase the usability of the results in the first part of the serial study. A previous study (Jung et al, 2021) confirmed that it is possible to estimate the reliable SHP potential through the application of the discharge simulation and blending technique that uses meteorological data even in ungauged basins without discharge data [8].…”
Section: Literature Reviewmentioning
confidence: 95%
See 3 more Smart Citations
“…The discharge was calculated using several runoff formulas and hydrologic models and blending techniques have been proposed to reduce the uncertainty of the results and to increase the usability of the results in the first part of the serial study. A previous study (Jung et al, 2021) confirmed that it is possible to estimate the reliable SHP potential through the application of the discharge simulation and blending technique that uses meteorological data even in ungauged basins without discharge data [8].…”
Section: Literature Reviewmentioning
confidence: 95%
“…To calculate the potential, it is necessary to prepare standard coefficients for the number of resources (natural environmental conditions), geographic conditions, technical elements (e.g., energy efficiency, operation rate, and collection rate), environmental performance, and technological progress through long-term data accumulation. Many studies have been conducted on the estimation of the SHP potential [8].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…References [33][34][35] compared the Kajiyama formula and TPM in terms of the accuracy of runoff estimation. They analyzed the performance of the models against the observed data.…”
Section: Inflow Estimationmentioning
confidence: 99%